Spatial Spillovers Revisited: Innovation, Human Capital and Local Dynamics - Baycan, Tuzin; Nijkamp, Peter; Stough, Roger (Wiley, 2017)
AbstractThis symposium focuses on understanding key territorial‐level innovation trends and processes by country, region and technology. It questions various widely accepted assumptions, offers fresh perspectives, both conceptually and methodologically, and challenges a paradigm shift in the field of innovation and spatial dynamics. It consists of three articles analysing at different scales (urban, regional and national) the territorial dynamics of innovation and their determinants. The innovation process, with local symbiosis and spatial spillovers at its core, is analysed within the conceptual framework of national and regional innovation systems and regional economic development. Based on a discussion of spatial spillovers and the way they shape the evolutionary and symbiotic relationships between local agents and actors, including university, industry and local development agencies, the symposium highlights the relevance of this framework for a better understanding of the transformation of local economic development processes. It investigates the differences in the geography of innovation regarding different institutional settings, different systems of innovation, and different national innovation strategies. While addressing mainly the EU, the US, and emerging countries such as China and India, the contributions also highlight the critical role of current innovation policies from a general perspective. In so doing, the symposium recognizes a contrarian perspective that argues that contemporary information and communication technologies (ICTs) provide a way to leapfrog the dominant role of proximity in innovation processes, creating a complimentary rather than a substitution effect for more remote and peripheral places. That said, this symposium focuses primarily on an urban network view of the innovation process and proximal effects in this context.